2011
DOI: 10.1089/bsp.2011.0020
|View full text |Cite
|
Sign up to set email alerts
|

The Key to Enabling Biosurveillance Is Cooperative Technology Development

Abstract: The world population will continue to face biological threats, whether they are naturally occurring or intentional events. The speed with which diseases can emerge and spread presents serious challenges, because the impact on public health, the economy, and development can be huge. The U.S. government recognizes that global public health can also have an impact on national security. This global perspective manifests itself in U.S. policy documents that clearly articulate the importance of biosurveillance in pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…This project demonstrated that a functional influenza surveillance system could be created by integrating the existing national IDSR systems (Kebede et al, 2013). International cooperation could significantly enhance biosurveillance efficiency (Emanuel et al, 2011). For example, international cooperation based on open-source genomic sharing accelerates the analysis of Shiga toxin-producing E. coli O104:H4, allowing results from Germany within a week (Rohde et al, 2011).…”
Section: International Deep Cooperation To Establish Global Surveilla...mentioning
confidence: 99%
“…This project demonstrated that a functional influenza surveillance system could be created by integrating the existing national IDSR systems (Kebede et al, 2013). International cooperation could significantly enhance biosurveillance efficiency (Emanuel et al, 2011). For example, international cooperation based on open-source genomic sharing accelerates the analysis of Shiga toxin-producing E. coli O104:H4, allowing results from Germany within a week (Rohde et al, 2011).…”
Section: International Deep Cooperation To Establish Global Surveilla...mentioning
confidence: 99%